Pandemi Covid-19 dalam Perspektif Teologi Pentakosta - Simon, Simon; Dully, Stefanus; Yulianto, Tomi; Wibowo, Adi Prasetyo (Pusat Studi Pentakosta Indonesia, 2021)
This paper discusses the pandami of COVID-19 in a Pentecostal theology perspective. The current pandemic is causing trouble for everyone, at the same time this epidemic encourages religious people to view and study from a theological point of view how this COVID-19 disease from the perspective of the Bible. This article was written using a qualitative method with a literature study approach. Within the internal of Christianity itself, the various interpretations of COVID-19 can be analyzed from a theological frame. In the perspective of Pentecostal theology, of course this pandemic is believed to be a part of the prophecy of the holy book as well as hinting that we are in an end-time phase, one of which is the epidemic of pestilence today. This pandemic is also within the framework of Pentecostal theology as preparation for the coming of Jesus Christ to earth, for the second time through pestilence as written by the Scriptures. This COVID-19 incident is also a phase in which humans will enter a period of queue for Kris who becomes the ruler and controller of this world. Key Words: Pandemic COVID-19, Pentecostal Theology, Church.Tulisan ini membahas pandemi COVID-19 dalam perspektif teologi Pentakosta. Pandemi yang terjadi saat ini tentu menyebabkan kesulitan bagi siapa saja, sekaligus wabah ini mendorong kaum religius untuk memandang dan mengkaji dari sudut pandang teologis bagaimana penyakit COVID-19 ini dari perspektif Kitab Suci. Artikel ini ditulis dengan menggunakan metode kualitatif dengan pendekatan studi kepustakaan. Di dalam lingkup internal Kekristenan sendiri, beragam pemaknaan dan penafsiran mengenai COVID-19 ini jika ditelisik dari bingkai teologis. Dalam perspektif teologi Pentakosta, tentu pandemi ini diyakini sebagai bagian dari nubuatan kitab suci sekaligus mengisyaratkan kita berada di fase akhir zaman yang ditandai salah satunya mewabahnya penyakit sampar di masa kini. Pandemi ini juga dalam bingkai teologi Pentakosta sebagai persiapan kedatangan Yesus Kristus ke bumi, untuk kedua kalinya melalui penyakit sampar sebagaimana yang ditulis oleh Kitab Suci. Peristiwa COVID-19 ini juga sebagai fase di mana manusia akan memasuki masa anti Kris yang menjadi penguasa dan pengendali dunia ini. Kata Kunc: Pandemi COVID-19, Teologi Pentakosta, Gereja,